PENGARUH PENGGUNAAN APLIKASI YOUTOBE BERBASIS STUDI KASUS UNTUK MENINGKATKAN KETRAMPILAN SISWA MTS BU GUPPI KOTA TEBING TINGGI PADA MATERI PRAKTIK SHOLAT DITINJAU DARI ASPEK VALIDITAS DAN PRAKTIKALITAS - Elvina Elvina; Al Afif Hazmar; Rian Vebrianto (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Prayer (shalat) practice learning at MTs BU GUPPI Tebing Tinggi City faces significant challenges due to limited interactive media and the difficulty of demonstrating movement-based skills through conventional teaching methods. This study aims to develop a case study-based YouTube application and examine its validity and practicality as a learning medium to improve students’ prayer practice skills. The research employed a Research and Development (R&D) method using the Four-D (4D) model, limited to the Develop stage, encompassing needs analysis, design, development, and testing of validity and practicality. The research subjects consisted of three expert validators (material, media, and language experts), two Islamic Education teachers, and 32 eighth-grade students of MTs BU GUPPI Tebing Tinggi City. Data were collected using validation and practicality questionnaires analyzed descriptively using percentage techniques. The results indicated that the case study-based YouTube application achieved an average validity score of 4.45 (89.00%), categorized as very valid across material, media, and language aspects. The practicality test yielded an average score of 4.53 (90.50%), categorized as very practical based on teacher and student evaluations. Observations further confirmed increased learning motivation, enhanced peer interaction, improved accuracy of prayer movements and recitations, as well as greater efficiency and flexibility in learning. This study contributes an innovative digital learning solution for Islamic Education teachers, particularly for psychomotor skill-based content such as prayer practice, and serves as a replicable model for integrating YouTube with case-based learning approaches in madrasah settings.